Pemanfaatan Drum Plastik Bekas sebagai Reaktor (Teknologi Tepat Guna) untuk Mengolah Sampah Rumah Tangga menjadi Kompos Organik - Fatkhul Amin (Jurnal Ilmiah Dinamika Teknik, 2008)
Every day household always produce kinds of rubbish like dry and wet rubbish papers which are thrown to the garbage can. This kind to change to improve our prosperity. Garbage is a worthy capital as it can he used as material which can be transformed into selling commodity. Applied technology is an alternative which is efficient enough for this time. The process of applied technology is very easy to carry out since all the equipments are available in our surrounding and the cost to make it is affordable, and more over applied technology can be made by using used things. The use used conlainer as reactor to transform garbage is applied technology which is not dangerous and is able to increase income so that later on the it can improve our prosperity.